PSYCHOLOGICAL CONDITIONS OF STUDENTS' ADAPTATION TO EDUCATION IN FOREIGN HIGH EDUCATION INSTITUTIONS - Voshkolup Hanna (Alfred Nobel University Publisher, 2023)
The article is devoted to the problem of substantiating the psychological conditions of students' adaptation to the conditions of study in foreign higher education institutions. The purpose of the article is to substantiate the psychological conditions for ensuring successful adaptation of students to study in foreign higher education institutions. The tasks of the article are defined as: elucidating the essence of the concept of "adaptation" in scientific psychological research; determination of psychological features of first-year students' adaptation to study at higher education institutions; substantiation of the factors of successful adaptation of students to study at foreign higher education institutions; substantiation of the psychological conditions of such adaptation within the limits of each of the specified factors. To achieve the goal, the following methods were used: literary analysis, generalization, comparison, systematization, etc. The article contains the following research results. Researching the theoretical foundations of the essence of the concept of "adaptation", it was found out that from a psychological point of view, the term "adaptation" (Latin adaptation - "adjustment", "adjustment") was first proposed in 1865 by the German physiologist G. Aubert and was initially more widespread in the medical and biological literature. Critical analysis of approaches to defining the essence of the concept of "adaptation" by various researchers was carried out. It has been defined that the psychological aspect of the "adaptation" category is much broader than in the biological and medical sciences. This is achieved thanks to the social task that psychology sets for adaptation (the need for an individual to adapt to a new social environment) and the importance of various types of activity for the implementation of this task. It is emphasized that the concept of "adaptation" is currently one of the key concepts in personality psychology in the direction of research into the conditions that ensure the possibility of its existence in the changing conditions of the surrounding environment. At the same time, such a process can take place during the entire life of an individual, since from time to time they have to adapt to various situations that appear in the environment of their life activities. Accordingly, the researchers call "man-nature" or "man-society" the main subjects of adaptation. At the same time, human adaptation to natural conditions is beyond the scope of this study. Therefore, we focus on human adaptation to society. It has been established that the adaptation of firstyear students to the conditions of study at higher education institutions depends on many factors, but the most influential ones are personal: the qualities of a person's character, their motives and aspirations, and the degree of realization of an active position as an indicator of successful full adaptation. In addition, from a psychological point of view, the process of adaptation of first-year students to study is realized under the condition of their active position, when they are aware of their social status and the new role behaviour inherent in it and, already on the basis of this understanding, realize their individual capabilities while solving general educational and professional problems and tasks. In such conditions, there is a more successful interaction with the new team and a detailed familiarization with the new duties; perception through oneself of stereotypes of behaviour in this educational environment; more complete adaptation to such an environment (assimilation) and, as the ultimate goal, identification of one's personal interests with collective ones. In addition to the purely adaptation issues of the transition of the learning process from school to higher education, it is suggested to consider and take into account the migration factor of such adaptation in order to more comprehensively define its psychological conditions. Taking into account the critical analysis of scientific works on the essence and factors of ensuring the successful adaptation of first-year students to study at higher education institutions, including taking into account migration processes and the need to study in foreign higher education institutions, we suggest taking into account the main two factors of such adaptation: general adaptation (related to the main problems of an educational nature that arise in students when starting the first year of study and mental rethinking of new study conditions) and migration (in addition is imposed on those students who enter foreign higher education institutions and, along with new educational conditions, are also forced to adapt to new social conditions of living in another country). At the same time, we consider the main psychological conditions to be: in terms of the general adaptation factor - adaptability, stress resistance, manageability, in terms of the migration factor - satisfaction with life and emotional stability.